An Examination of Meaningful Experiences During Sport Education - Alshuraymi, Ali Nasser; Hastie, Peter (Physical Education and Sports: Studies and Research, 2024)
Background: In recent research years, there has been an increasing focus on the meaningfulness of physical education experiences. While it has been suggested that certain curriculum models such as sport education or cooperative learning provide opportunities for meaningful engagement in physical education, to date there has been no empirical study of those claims. Objectives: The purpose of this study was to quantitatively examine students’ perceptions of meaningfulness in two physical education contexts: traditional multi-activity format, and sport education. Methods: Sixty seventh-grade students aged 12 to 14 completed a 20-item survey titled "Meaningful Experiences in Physical Education Survey (MEPES)" prior to and at the completion of one of three sport education seasons. The analysis consisted of independent samples t-test comparisons between the two contexts (previous physical education experiences, and sport education) for each of the five dimensions of meaningfulness. A Pearson correlation was conducted to examine if there were significant relationships between the five dimensions. Results: Results of the independent samples t-test showed that significantly higher levels of meaningfulness were identified from participation in sport education than in previous physical education for four of the five dimensions. Pearson's coefficient results indicated significant positive correlations between all five meaningfulness dimensions. Conclusion: Sport education has structural elements that promote a sense of meaningfulness within physical education.